The multiple landscapes of Biedjovággi: Ontological conflicts on indigenous land. (16th September 2021) - Kramvig, Britt; Avango, Dag
Abstract: In this article, we engage with environmental conflicts on indigenous land through a focus on an attempt to gain social licence to reopen and operate the Biedjovággi mine in Guovdageainnu/Kautokeino in Sápmi, Norway. We argue that mining prospects bring forth ontological conflicts concerning land use, as well as ways to know the landscape and the envisioned future that the land holds. It is a story of a conflict between two different ways of knowing. The paper explores the Sámi landscape through different concepts, practices and stories. We then contrast this to the way the same landscape is understood and narrated by a mining company, through the programmes and documents produced according to the Norwegian law and standards. We follow Ingold's argument that the Sámi landscape practices are taskscapes, where places, times and tasks are interconnected. These were not acknowledged in the plans and documents of the mining company. We conclude by addressing the tendency of extractive industries to reduce different landscapes in ways that fit with modern understandings, which oppose culture to nature.